Extravasation of Cytotoxic Agents Compendium for Prevention and Management - Mader, Ines. (Springer Vienna : Imprint: Springer, 2010)
The extravasation of cytotoxic agents can result in severe local tissue damage and medical emergencies during tumour therapy. This revised compendium is intended to help clinicians assess any situation speedily and with certainty. The general section of the book includes topics such as predisposition, prevention, type of harm, general measures in handling extravasated drugs, specific antidotes, and documentation. In the 2nd edition, the scientific information contained in the general section and relating to the actual substances has been updated. The substance specific part of the book includes detailed instructions on handling more than 50 cytotoxic drugs, to initiate targeted measures. Templates for an extravasation set, overview tables, documentation sheets, and patient information, as we as a CD-ROM are included to support clinical practice. The book is the outcome of a consensus of an interdisciplinary working group that has collected and systematically reviewed all published literature on the topic.